Association between Alpha- Klotho Protein, Calcium, and Phosphate concentrations in Adult Iraqi Patients with Beta-Thalassemia Major - Kadhim, Ahmed J.; El-Yaseen, Hedef D.; Jawad, Ali M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Beta-thalassemia major is a prevalent global condition characterized by a rapid breakdown of red blood cells. Regular blood transfusions can give rise to problems such as cardiovascular disease, diabetes, osteoporosis, and renal disorders. Alpha-Klotho protein is a protein that has anti-aging properties and is involved in several functions, including reducing oxidative stress, regulating energy metabolism through several routes, and managing calcium and phosphate metabolism.Objective: This study aimed to assess changes in calcium and phosphate levels, Alpha-Klotho protein concentration, and their associations with cardiac dysfunction in patients with Beta-thalassemia major.Methods: The study was conducted at Al-Sadr General Hospital and Ibn Albaladi Center of Blood Diseases, Baghdad, and involved 90 participants who were grouped into three groups: Group A: 30 patients with Beta-thalassemia major and heart dysfunction; Group B:30 patients with Beta-thalassemia major without any signs of heart dysfunction; and Group C:30 healthy individuals as a control group. The indicators examined were serum levels of Alpha-klotho protein, calcium, phosphate, and Ferritin. ELISA method was used to assess serum Alpha-klotho protein, whereas serum Ca, serum phosphate, and serum Ferritin were analyzed using the Beckman Coulter AU clinical chemistry analyzers.Results: The mean values of Serum Alpha-Klotho protein, phosphate, and Ferritin in the patients with beta-thalassemia were greater than those in the control group with P value